Connecting students and researchers: the secondary school student's voice in foreign language education research. Issue 4 (3rd July 2020) - Bloemert, Jasmijn; Paran, Amos; Jansen, Ellen
ABSTRACT: The inclusion of student voice in foreign language research often relies mainly on a perspective that includes their voice as a data source, in spite of claims that the perspectives that include students as initiators should be at the fore. In this paper, the authors address the incongruity of this situation, arguing for a revision of current views. They discuss different conceptualisations of student voice in educational research, and argue that combinations of different perspectives on student voice provide unique insights that are necessary to develop our knowledge base. They then provide a detailed account of an empirical study in which an English as a foreign language (EFL) literature teaching and learning model was validated through collaboration and co-construction with secondary school students. They demonstrate the ways in which two different perspectives were combined within the project, resulting in a dialogical process, which then lends multidimensional support to the findings.